2017
DOI: 10.1111/pce.12949
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal modulation of abscisic acid and gibberellin metabolism and signalling mediates the effects of suboptimal and supraoptimal temperatures on seed germination in wheat (Triticum aestivum L.)

Abstract: Seed germination is a complex process regulated by intrinsic hormonal cues such as abscisic acid (ABA) and gibberellin (GA), and environmental signals including temperature. Using pharmacological, molecular and metabolomics approaches, we show that supraoptimal temperature delays wheat seed germination through maintaining elevated embryonic ABA level via increased expression of ABA biosynthetic genes (TaNCED1 and TaNCED2), increasing embryo ABA sensitivity through upregulation of genes regulating ABA signallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 56 publications
3
59
0
2
Order By: Relevance
“…On the other hand, imbibition of extremely dormant OS38 grains at a low temperature increased ABA levels by inducing the expression of TaNCED (ABA biosynthesis) gene and suppressing TaGA3ox2 and TaABA8 OH2 genes. In a recent study, Izydorczyk et al [127] observed a delay in germination of non-dormant imbibed wheat seeds under supra-optimal and suboptimal temperatures which was due to the expression of ABA signaling genes; ABI3, ABI5, PYL5, and SnRK2 in the embryo tissues resulted in enhanced ABA sensitivity. These studies explained the role of ABA and GA in dormancy and germination but needs further genetic studies to understand the physiological role of metabolic genes of ABA and GA in the regulation of seed dormancy in cereal crops.…”
Section: Environmental Factors Affecting Phs Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, imbibition of extremely dormant OS38 grains at a low temperature increased ABA levels by inducing the expression of TaNCED (ABA biosynthesis) gene and suppressing TaGA3ox2 and TaABA8 OH2 genes. In a recent study, Izydorczyk et al [127] observed a delay in germination of non-dormant imbibed wheat seeds under supra-optimal and suboptimal temperatures which was due to the expression of ABA signaling genes; ABI3, ABI5, PYL5, and SnRK2 in the embryo tissues resulted in enhanced ABA sensitivity. These studies explained the role of ABA and GA in dormancy and germination but needs further genetic studies to understand the physiological role of metabolic genes of ABA and GA in the regulation of seed dormancy in cereal crops.…”
Section: Environmental Factors Affecting Phs Resistancementioning
confidence: 99%
“…Several studies have reported the regulatory mechanisms of other hormones like ethylene, jasmonate, brassinosteroids, and auxin in controlling seed dormancy, germination and PHS resistance [43,121,124,125]. Environmental Agronomy 2019, 9, 117 6 of 29 factors, such as light and temperature, also affect the dormancy and germination by disturbing the balance between ABA and GA levels in cereal crops [126,127].…”
Section: Plant Growth Hormonesmentioning
confidence: 99%
“…Gibberellin is an antagonist of abscisic acid, and both hormones are crucial for germination control. Their proportions, and thus, the seed germination ability, may be considerably modified by external factors, such as temperature (Izydorczyk et al, 2018), due to which low or high temperature treatment is often used to stimulate germination (Arslan et al, 2011;Morozowska, 2002). Our study demonstrated synergistic effects of low temperature in presowing stratification and GA 3 treatment in P. farinosa seeds.…”
Section: Optimization Of Seed Germinationmentioning
confidence: 99%
“…Так, за високого вмісту ендогенної АБК й низького гіберелінів насіння переходить у стан спокою, тоді як за низького рівня АБК й високого гіберелінів -індукуються дозрівання й проростання насіння. Баланс регулюється на рівні синтезу гормонів і балансу їхніх сигнальних каскадів [36,[48][49][50]. Повідомлялося, що AБК пригнічує біогенез гіберелінів [48].…”
unclassified
“…Гібереліни також негативно впливають на синтез АБК під час проростання насіння [45]. Показано, що на баланс між АБК і гіберелінами впливають температура, освітлення та активні форми кисню, утворення яких розглядають як ендогенний сигнальний фактор [50][51][52]. Проростання насіння контролюють гени спокою QTL DOG1, а також відповідальні за синтез гіберелінів GID1A і GID1C й АБК ABI3, ABI1, ABI5 гени, які контролюють схожість [36,53].…”
unclassified